An efficient approach to the quantitative analysis of humic acid in water. (1st January 2016) - Wang, Xue; Li, Bao Qiong; Zhai, Hong Lin; Xiong, Meng Yi; Liu, Ying
Highlights: Zernike moments of grayscale image were used to the quantitative analysis. Reliable linear quantitative model with selected Zernike moments was established. The obtained results were more satisfactory than that of N-PLS and ATLD methods. The proposed method is immune from the scattering and noise signals well. Our strategy could be extended to the analysis of other 3D spectra. Abstract: Rayleigh and Raman scatterings inevitably appear in fluorescence measurements, which make the quantitative analysis more difficult, especially in the overlap of target signals and scattering signals. Based on the grayscale images of three-dimensional fluorescence spectra, the linear model with two selected Zernike moments was established for the determination of humic acid, and applied to the quantitative analysis of the real sample taken from the Yellow River. The correlation coefficient ( R 2 ) and leave-one-out cross validation correlation coefficient ( R 2 cv ) were up to 0.9994 and 0.9987, respectively. The average recoveries were reached 96.28%. Compared with N-way partial least square and alternating trilinear decomposition methods, our approach was immune from the scattering and noise signals owing to its powerful multi-resolution characteristic and the obtained results were more reliable and accurate, which could be applied in food analyses.